Cancer immunotherapy with PI3K and PD-1 dual-blockade via optimal modulation of T cell activation signal. Issue 8 (25th August 2021) - Isoyama, Sho; Mori, Shigeyuki; Sugiyama, Daisuke; Kojima, Yasuhiro; Tada, Yasuko; Shitara, Kohei; Hinohara, Kunihiko; Dan, Shingo; Nishikawa, Hiroyoshi
Abstract : Background: Immune checkpoint blockade (ICB) induces durable clinical responses in patients with various types of cancer. However, its limited clinical efficacy requires the development of better approaches. In addition to immune checkpoint molecules, tumor-infiltrating immunosuppressive cells including regulatory T cells (Tregs) play crucial roles in the immune suppressive tumor microenvironment. While phosphatidylinositol 3-kinase (PI3K) inhibition as a Treg-targeted treatment has been implicated in animal models, its effects on human Tregs and on the potential impairment of effector T cells are required to be clarified for successful cancer immunotherapy. Methods: The impact of a selective-PI3K inhibitor ZSTK474 with or without anti-programmed cell death 1 (PD-1) monoclonal antibody on Tregs and CD8 + T cells were examined with in vivo animal models and in vitro experiments with antigen specific and non-specific fashions using peripheral blood from healthy individuals and cancer patients. Phenotypes and functions of Tregs and effector T cells were examined with comprehensive gene and protein expression assays. Results: Improved antitumor effects by the PI3K inhibitor in combination with ICB, particularly PD-1 blockade, were observed in mice and humans. Although administration of the PI3K inhibitor at higher doses impaired activation of CD8 + T cells as well as Tregs, the optimization (doses and timing) of this combination treatment selectively decreased intratumoral Tregs, resulting in increased tumor antigen-specific CD8 + T cells in the treated mice. Moreover, on the administration of the PI3K inhibitor with the optimal dose for selectively deleting Tregs, PI3K signaling was inhibited not only in Tregs but also in activated CD8 + T cells, leading to the enhanced generation of tumor antigen-specific memory CD8 + T cells which contributed to durable antitumor immunity. These opposing outcomes between Tregs and CD8 + T cells were attributed to the high degree of dependence on T cell signaling in the former but not in the latter. Conclusions: PI3K inhibitor in the combination with ICB with the optimized protocol fine-tuned T cell activation signaling for antitumor immunity via decreasing Tregs and optimizing memory CD8 + T cell responses, illustrating a promising combination therapy.